March to Armageddon : the United States and the nuclear arms race, 1939 to the present - Powaski, Ronald E. (Oxford University Press, 1987)
This book traces the evolution of the nuclear arms race from its origin in Roosevelt's decision to develop an atomic bomb to Reagan's decision to continue its expansion in the 1980s.